The visual appearance of beer: A review concerning visually-determined expectations and their consequences for perception. (December 2019) - Van Doorn, George; Timora, Justin; Watson, Shaun; Moore, Chris; Spence, Charles
Abstract: This review critically evaluates the literature concerning the impact of visual appearance cues (including colour, foam, and cloudiness) on people's perception in the beer category. The authors assess both the sensory expectations that are elicited by the visual appearance of beer, and the extent to which those expectations carry-over to influence the actual tasting experience. Beer is a particularly intriguing category to study since the differing production rules in different countries mean that there is not always the same scope to modify the colour in order to meet perceived consumer demands. What is more, there is currently disagreement in the literature concerning the impact of beer colour and foam on people's expectations of beer prior to tasting, and their multisensory flavour perception on tasting. Given how much beer is consumed annually, it is surprising that more research has not been published that assesses the undoubtedly important role of visual appearance in this beverage category. Part of the reason for this may simply be that it is difficult to create consistent experimental stimuli given the rapid transition of the head of the beer post-serving. Highlights: Visual appearance cues influence people's expectations, but their influence on perception is somewhat inconsistent. People generally expect darker-looking beers to be more bitter than lighter beers. The use of finings to improve clarity has no effect on flavour ratings, but people prefer the appearance of these beers. A moderate level of head and lacing generally has a positive influence on expected quality and drinkability.